Introdução à Teoria Ergódica - Moreira de Oliveira, Kaique Micael (2023)
This Final Course Paper presents an introduction to Ergodic Theory, focusing on the important Poincaré Recurrence Theorem. Here, the theory necessary for the demonstration of this theorem is developed, starting with an introduction to Measure Theory. Some of the applications of Ergodic Theory are also presented.